2018
DOI: 10.1111/bjd.16126
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anti-tumour necrosis factor-induced skin lesions reveals strong T helper 1 activation with some distinct immunological characteristics

Abstract: New-onset anti-TNF-α-induced eruptions previously classified as psoriasis or spongiotic dermatitis (eczema) exhibit a molecular profile that is different from either of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 57 publications
3
31
0
1
Order By: Relevance
“…Moreover, Stoffel et al . reported that EE induced by anti‐TNF‐α showed high levels of IL‐22, not only when compared with psoriasiform lesions that occurred with anti‐TNF‐α treatment, but also compared with conventional psoriasis and eczema lesions . Indeed, IL‐22 has been demonstrated to promote epidermal hyperplasia and to inhibit epidermal differentiation in spongiotic lesions .…”
Section: Clinical Features Of Patients With Eczematous Eruption (Ee)mentioning
confidence: 99%
“…Moreover, Stoffel et al . reported that EE induced by anti‐TNF‐α showed high levels of IL‐22, not only when compared with psoriasiform lesions that occurred with anti‐TNF‐α treatment, but also compared with conventional psoriasis and eczema lesions . Indeed, IL‐22 has been demonstrated to promote epidermal hyperplasia and to inhibit epidermal differentiation in spongiotic lesions .…”
Section: Clinical Features Of Patients With Eczematous Eruption (Ee)mentioning
confidence: 99%
“…Several studies demonstrated a clinically significant improvement for patients with AD underwent treatment with TNF‐α blockers . However, there is also a report mentioned anti‐TNF‐α–induced AD . Therefore, the precise mechanism of TNF‐α in the pathogenesis of AD is still plausible, which remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Der Ausdruck "anti-TNF-α-induzierte(s) Psoriasis/Ekzem" wurde durch die zutreffendere Bezeichnung "psoriasis-/eczema-like drug-related skin eruption" ersetzt. In einer kleinen Studie konnte gezeigt werden, dass sich anti-TNF-α-induzierte Psoriasis-ähnliche Hautläsionen in wesentlichen molekularen und zellulären Charakteristika von genuiner Psoriasis sowie von Dermatitis/Ekzem unterscheiden [229]. Nachdem das klinische Bild medikamentös induzierter Psoriasis-ähnlicher Läsionen häufig unklar und schwer von einer Dermatitis bzw.…”
Section: Psoriasis-ähnliche Und Ekzem-ähnliche Anti-tnf-α-assoziierteunclassified